Mentoring in education: an analysis of international practices and their implementation in Russia - N. V. Tikhonova; F. L. Ratner; I. Y. Vergasova (Russian State Vocational Pedagogical University, 2024)
Introduction. In the context of an ongoing discussion about the necessity to enhance the institution of mentoring in Russia, the examination and critical analysis of the experiences of countries where the system of mentoring for novice teachers is regulated at the state level is of undeniable interest. Aim. The study aimed to identify the main features of mentoring in France and determine the potential for applying international experience in the Russian educational system. Methodology and research methods. The research employed the following methods: an analysis of pedagogical literature and normative documents in the field of education in France, and a questionnaire survey of novice teachers working as trainee teachers in primary schools in Paris. As a survey technique, a continuous online survey with a group was employed. Results and scientific novelty. The process of becoming a fully qualified lower primary teacher in France is outlined: it involves passing a competitive examination (CRPE) and successfully completing a probation period. During this probation period, candidates are required to work for one year in a school as a trainee teacher under the guidance of mentor teachers. The research focuses on mentoring practices in France, the pathways to becoming a new teacher mentor, their job requirements, professional training, certification processes, as well as their roles and responsibilities. Based on the results of a survey of trainee teachers, a social profile of a novice teacher in France was created. The main challenges and shortcomings of the participants were identified, and their interactions with mentors were analysed. The collected data enabled the authors to emphasise the benefits of the French education policy regarding entry into the teaching profession and to formulate recommendations for mentor selection and training in Russia. Practical significance. The content of the article will be beneficial for specialists in the field of comparative education and for members of the scientific and pedagogical community engaged in teacher training programmes.